Analysis and Design of an Active-Clamping Coupled-Inductor Boost Converter for High-Voltage-Gain Applications - Rodycz, Helder M.; Jr., Eloi Agostini (Eletrônica de Potência, 2018)
This paper proposes the analysis and design of an active-clamping coupled- inductor boost converter for high-voltage-gain applications. A buck-boost type active clamping circuit is employed in a configuration that enables the leakage energy to be recycled to the output. An accurate mathematical analysis considering the influence of the leakage and auxiliary inductances in the energy transfer process is carried out, providing the basis for the elaboration of a step- by-step design procedure. A detailed commutation analysis is also performed, describing the necessary conditions for soft-switching operation. The theoretical results are experimentally verified with a 260 W, 30 V input voltage, 400 V output voltage, 100 kHz, 94.38% peak efficiency prototype.